USE OF FOOD RESOURCES BY DETRITIVOROUS FISH IN FLOOD-PLAINS: A SYNTHESIS (2015)
The present review investigated the sources of energy for detritivorous fish species in floodplains. Recent studies have shown that environmental changes that alter the terrestrial vegetation affect essentially the resource base in these areas, such as the detritus. In aquatic environments, especially floodplains, a major part of metabolic processes is supported by terrestrial detritus, which accounts for maintaining the detritivorous food chain. Thus, one way to evaluate environments changes is through isotopic studies of organic matter, which allows acquiring information about the quantity and quality of organic matter. This approach is required for understanding the interactions between the organic matter dynamics and its ecological effects, allowing the monitoring of these resources. However, researches on the energy flow in food chains should also employ an approach that quantifies the magnitude of these food subsidies, as also the access routes of aquatic consumers, in watersheds of different sizes and in diverse land uses.El uso de los recursos alimenticios por peces detritívoros en planicies de inundación: una síntesisResumenEsta revisión procuró investigar las fuentes de energía para las especies de peces detritívoras en la llanura de inundación. Los estudios han demostrado que las transformaciones ambientales que causan los cambios en la vegetación terrestre afectan principalmente la base de los recursos en estos planos inundables, tales como el detritus. En los ambientes acuáticos, especialmente las llanuras de inundación, la mayoría de los procesos metabólicos están sustentados por el detritus terrestre, y esta función es responsable de mantener las redes detritívoras. Una forma de evaluar estos cambios es a través de estudios isotópicos de la materia orgánica, los cuales permiten obtener información sobre su cantidad y su calidad mediante el análisis de la biomasa microbiana. Este enfoque es necesario para comprender las interacciones entre la dinámica de la materia orgánica y sus efectos ecológicos, lo que permite a su vez la valoración de estos recursos. Sin embargo, se concluye que los estudios futuros también deben cuantificar la magnitud de estos subsidios energéticos, asícomo las vías de acceso de los consumidores acuáticos, lo cual debe evaluarse en cuencas hidrográficas de diferentes tamaños y con diversos usos de la tierra.